2021
DOI: 10.3390/constrmater1020007
|View full text |Cite
|
Sign up to set email alerts
|

A Decommissioned Wind Blade as a Second-Life Construction Material for a Transmission Pole

Abstract: This paper demonstrates the concept of adaptive repurposing of a portion of a decommissioned Clipper C96 wind turbine blade as a pole in a power transmission line application. The current research program is aimed at creating a path towards sustainable repurposing of wind turbine blades after they are removed from service. The present work includes modelling and analysis of expected load cases as prescribed in ASCE 74 and NESC using simplified boundary conditions for tangent pole applications. Load cases invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The authors have tested the structural analyses for different load cases: extreme wind, concurrent ice, and wind; extreme ice, differential ice, broken conductor, and broken shield; and governing load cases for bending, shear, and torsion. The results showed that the blade pole can resist the expected loads with reasonable safety factors and that the expected deflections are within permissible limits [46].…”
Section: Upcycling Wind Turbine Bladesmentioning
confidence: 87%
“…The authors have tested the structural analyses for different load cases: extreme wind, concurrent ice, and wind; extreme ice, differential ice, broken conductor, and broken shield; and governing load cases for bending, shear, and torsion. The results showed that the blade pole can resist the expected loads with reasonable safety factors and that the expected deflections are within permissible limits [46].…”
Section: Upcycling Wind Turbine Bladesmentioning
confidence: 87%
“…Next on the waste hierarchy is blade repurposing, which involves the reuse of full blades or large sections of the blade in new industrial or architectural applications. Some examples of repurposing applications include pedestrian bridges (e.g., Blade Bridge along the Midleton-Youghal Greenway in County Cork, Ireland) [22,54,55], power transmission lines [56], children's playgrounds (e.g., Wikado playground, Rotterdam) [57], bicycle shelters (e.g., Aalborg Harbour) [58], affordable housing [41], among others [59]. Full blade repurposing implies that the entire blade will be reused in one or more applications and will therefore yield a 100% reuse potential.…”
Section: Recycling Technologies and Potential Materials That Can Be '...mentioning
confidence: 99%
“…Repurposing these blades to new structural applications minimises the waste in a landfill [95]. Wind turbine blades are also proposed to be used in electric transmission towers [93,94,96], as seen in Figure 5. Wind turbine blades have also been employed in secondary applications, such as playgrounds and bus shelters in The Netherlands [97].…”
Section: Reuse or Repurposementioning
confidence: 99%